From abstraction to unsaying: how the Eunomian controversy changed Gregory of Nyssa’s aphairetic ethics to an apophatic ethics - Steenbuch, Johannes Aakjær (Vox Patrum, 2018)
In early Christian thinking negative theology was often applied for polemical purposes, as a means of asserting the Christian distinction between God and everything else. Only later did negative theology develop into a philosophical and contemplative method. But even then it often kept a polemical function. This was the case for Gregory of Nyssa who applied forms of negative theology in his spiritual and exegetical works as well as in his polemical works, especially those against Eunomius. Using a distinction between aphairetic and apophatic kinds of negative theology, it can be argued that Gregory’s theology, epistemology and philosophy of language, as developed during the Eunomian controversy, changed his negative theology in a fundamental way from an aphairetic theology, based on abstraction, to a thoroughly apophatic theology, based on negation in the sense of unsaying. It can further be argued that the results of this development influenced Gregory’s ethical theories, his moral epistemology in particular. The main texts in question, besides Gregory’s writings against Eunomius, are his early work on the inscriptions of the Psalms and his later work on the life of Moses. Both contain reflections on Moses’ spiritual development, but while the former uses mostly affirmative language, the latter involves a much higher degree of apophatic theology. This change is likely to have occurred during the Eunomian controversy where such things as God’s infinity and the inability of human beings to grasp the divine essence became fundamental in such a way that apophatic, rather than aphairetic, language and thinking gained a central role in Gregory’s theology as well as ethics.